Design and Characterization of a Self-Oscillating Fluxgate-Based Current Sensor for DC Distribution System Applications - Wei Chen; Huaijie Chen; Haibo Xu; Li Li (Sensors)
Fluxgate-based current sensors are usually implemented for DC current detection, but their complex structure and circuits with large volume and high cost have been limiting their applications. This paper presents a low-cost sensor with a one-core-three-winding structure that can be suitable for integrated measurement in distribution system applications. Based on a self-oscillating scheme, the new sensor introduces an induction winding to suppress the noise caused by the transformer effect instead of adding more magnetic cores. The transmission and transfer functions of the sensor, based on nonlinear magnetization, are conducted for the qualitative and quantitative analysis. A prototype is fabricated and several specifications including linearity, small-signal bandwidth, output noise, and power-on repeatability are characterized. Experimental results show that the proposed sensor realizes an accuracy better than 0.15% with a range of 0–600 A. By implementing the proposed noise suppression method, the signal-to-ratio is improved from 19.55 dB to 48.88 dB. Compared with a traditional fluxgate sensor with a three-core-four-winding structure, the proposed sensor reduces the volume by 44.4% and the cost by 23.6%, indicating a good prospect for practical applications.